First total synthesis of hunanamycin A - Shingare, Rahul D.; Velayudham, R.; Gawade, Jalindar R.; Reddy, D. Srinivasa (Organic Letters, 2013)
The first total synthesis of hunanamycin A, an antibiotic natural product with a pyrido[1,2,3-de]quinoxaline-2,3-dione core from a marine-derived Bacillus hunanensis, is disclosed. The present effort provides access to sufficient amounts of scarce hunanamycin A for further biological evaluation and confirmation of the assigned absolute configuration. In addition, four new analogues of the natural product are reported.